Design of high-brightness TEM00-mode solar-pumped laser for renewable material processing - Liang, Dawei (2014)
The conversion of sunlight into laser light by direct solar pumping is of ever-increasing importance because broadband, temporally constant, sunlight is converted into laser light, which can be a source of narrowband, collimated, rapidly pulsed, radiation with the possibility of obtaining extremely high brightness and intensity. Nonlinear processes, such as harmonic generation, might be used to obtain broad wavelength coverage, including the ultraviolet wavelengths, where the solar flux is very weak. The direct excitation of large lasers by sunlight offers the prospect of a drastic reduction in the cost of coherent optical radiation for high average power materials processing. This renewable laser has a large potential for many applications such as high-temperature materials processing, renewable magnesium-hydrogen energy cycle and so on. We propose here a scalable TEM00 mode solar laser pumping scheme, which is composed of four firststage 1.13 m diameter Fresnel lenses with its respective folding mirrors mounted on a two-axis automatic solar tracker. Concentrated solar power at the four focal spots of these Fresnel lenses are focused individually along a common 3.5 mm diameter, 70 mm length Nd:YAG rod via four pairs of second-stage fused-silica spherical lenses and third-stage 2D-CPCs (Compound Parabolic Concentrator), sitting just above the laser rod which is also double-pass pumped by four V-shaped pumping cavities. Distilled water cools both the rod and the concentrators. 15.4 W TEM00 solar laser power is numerically calculated, corresponding to 6.7 times enhancement in laser beam brightness.